A study on milk adulteration of Savar Upazila in Bangladesh - Moonajilin, M. Sabrina; Saiful Islam, M.; Paul, Ratna (International Journal Of Community Medicine And Public Health, 2018)
Background: Milk adulteration has become a serious concern. Some of the adulterants in milk have serious adverse health effects. This study was designed to assess consumer awareness about milk and determine formalin and melamine in milk. Methods: The study involved a laboratory-based investigation and a survey was conducted to assess consumer awareness about milk adulteration from January 2018 to June 2018. Total 10 samples were collected from local market purposively. 2 adulteration tests were conducted to detect formalin and melamine in samples. 10 brands of milk from 8 companies were collected from different markets of Savar and tested at BCSIR as per Bangladesh Standards. On the other hand; a survey was conducted to assess consumer awareness about milk adulteration. A pre tested semi structured questionnaire, was used to collect the information. Statistical analysis was done by using Excel. Results: We found the concentration of formaldehyde and melamine in all 10 analyzed products below the level of detection. The majority (55.9%) of the respondents knew that there is a law in the country that deals with milk adulteration; among them 41.7% thought that the reduced mobile court activity is reason for unchanged milk adulteration situation and insufficient penalty is also a major factor (45%). Only (55.9%) respondents consider water is main milk adulterant and 31.8% know about Chemicals. The majority of the respondents 87.8% strongly agreed that milk adulteration has harmful effects on health. Conclusions: These findings may be helpful for the concerned government regulatory bodies to monitor the quality of the commercial milk in the market.